Titanium Dental Implant Corrosion: Mechanisms, Effects, and Preventive Strategies - Eko Budiyanto; Lukito Dwi Yuono (Asian Journal of Mechanical Engineering, 2025)
Titanium and its alloys are widely employed in dental implantology due to their favorable mechanical properties, corrosion resistance, and excellent biocompatibility, which are primarily attributed to the formation of a stable surface titanium dioxide (TiO2) passive layer. Despite these advantages, titanium dental implants are not completely immune to corrosion in the complex and dynamic oral environment. Variations in pH, presence of aggressive ions such as fluoride and chloride, microbial activity, mechanical loading, and micromovements at the implant–bone interface can disrupt the passive oxide layer and initiate corrosion processes. This degradation may result in the release of metallic ions and particles into peri-implant tissues, potentially triggering inflammatory reactions, hypersensitivity responses, bone resorption, and implant failure. This review comprehensively discusses the fundamental mechanisms of corrosion affecting titanium dental implants, including galvanic, pitting, crevice, fretting corrosion, and tribocorrosion. The biological and clinical consequences of corrosion products on peri-implant soft and hard tissues are critically analyzed, with emphasis on their role in peri-implantitis and aseptic implant loosening. Furthermore, current preventive strategies aimed at minimizing corrosion are examined, including implant material selection, surface modification techniques, protective coatings, and optimization of prosthetic design. Understanding the interplay between electrochemical, mechanical, and biological factors governing titanium implant corrosion is essential for improving long-term implant performance and clinical outcomes.